Potassium Recovery Potential of Selected Agroforestry and Organic Wastes in Ibadan, Nigeria - F., Akindejoye; T.B., Hammed; M.K.C., Sridhar (European Scientific Journal, ESJ, 2017)
This study explored potassium recovery from agroforestry wastes that may be a cheap alternative to imported ones. The wastes: Plantain Peel (PP), Coconut Fibre (CF), Coconut Shell (CS), Cocoa Pod (CP), Sugarcane Bagasse (SB), Sawdust (SD) and four common wood-fuel species - Antiaris toxicaria (Wd1), Cordia millenii (Wd2), Khayas senegalensis (Wd3) and Milicia excelsa (Wd4) were assessed for their ash content (AC) and moisture content (MC), using standard procedures of AOAC. Atomic Absorption spectrophotometer was used to determine mineral concentrations: potassium, sodium, magnesium, calcium, zinc, lead and iron of the wastes. In addition, efficacy of three methods of extracting potassium from ashes: cold water extraction at 35 OC, hot water extraction at 90 OC and steam extraction was assessed. Data were analysed using descriptive statistics and correlation test at p˂0.05. Wastes with highest values in terms of AC and MC were: CP (AC- 11.62 ± 0.3 %) and SB (MC- 82 ± 2.64 %). The highest concentration of K (mg·kg -1 ) was found in CP (8,387.50 ± 2.00 mg·kg-1 ). Cold water extraction gave the most potassium yield (88.44 %) and the highest solid potash content was found in PP (68 500 mg·kg -1 ) while CP had the highest K concentration (12.51±0.20 g·dm-3 ). Cocoa pod, plantain peel and Cordia millenii are very good sources of agroforestry/organic wastes for local production of potassium both in terms of solid potash yield and potassium recovery potential. Development of a suitable technology which can be used to extract potassium locally is recommended.